Design and preliminary verification of a novel powered ankle-foot prosthesis: From the perspective of lower-limb biomechanics compared with ESAR foot - Liu J.; Liu J.; Cheah P.Y.; Kouzbary M.A.; Kouzbary H.A.; Yao S.X.; Shasmin H.N.; Arifin N.; Razak N.A.A.; Osman A.A. (Public Library of Science, 2025)
A novel powered ankle-foot prosthesis is designed. The effect of wearing the novel prosthesis and an energy-storage-and-return (ESAR) foot on lower-limb biomechanics is investigated to preliminarily evaluate the design. With necessary auxiliary materials, a non-amputated subject (a rookie at using prostheses) is recruited to walk on level ground with an ESAR and the novel powered prostheses separately. The results of the stride characteristics, the ground reaction force (GRF) components, kinematics, and kinetics in the sagittal plane are compared. Wearing the powered prosthesis has less prolongation of the gait cycle on the unaffected side than wearing the ESAR foot. Wearing ESAR or proposed powered prostheses influences the GRF, kinematics, and kinetics on the affected and unaffected sides to some extent. Thereinto, the knee moment on the affected side is influenced most. Regarding normal walking as the reference, among the total of 15 indexes, the influences of wearing the proposed powered prosthesis on six indexes on the affected side (ankle's/knee's/hip's angles, hip's moment, and Z- and X-axis GRF components) and five indexes on the unaffected side (ankle's/knee's/hip's angles and ankle's/hip's moments) are slighter than those of wearing the ESAR foot. The influences of wearing the powered prosthesis on two indexes on the unaffected side (knee's moment and X-axis GRF component) are similar to those of wearing the ESAR foot. The greatest improvement of wearing the powered prosthesis is to provide further plantarflexion after reaching the origin of the ankle joint before toe-off, which means that the designed powered device can provide further propulsive power for the lifting of the human body's centre of gravity during walking on level ground. The results demonstrate that wearing the novel powered ankle-foot prosthesis benefits the rookie in recovering the normal gait more than wearing the ESAR foot. Copyright: ? 2024 Liu et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.